Extracranial-intracranial bypass surgery for occlusive atherosclerotic disease of the anterior cerebral circulation: protocol for a systematic review and meta-analysis - Xuesong Bai; Yao Feng; Kun Yang; Tao Wang; Jichang Luo; Xue Wang; Feng Ling; Yan Ma; Liqun Jiao (Systematic Reviews, 2020)
Abstract Background Occlusive atherosclerotic disease of the anterior cerebral circulation is one of the most common causes of anterior circulation ischemia and stroke. Treatment options include medical therapies (including antiplatelet use, blood pressure control, lipid reduction, and lifestyle modification) and extracranial-intracranial bypass surgery (such as superficial temporal artery-middle cerebral artery bypass). However, the optimal treatment remains unclear. The objective of this study will be to compare the efficacy of and extracranial-intracranial bypass surgery with that of other medical therapy in adult patients with occlusive atherosclerotic disease of the anterior cerebral circulation. Methods This is the study protocol for a systematic review. We will search MEDLINE, EMBASE, Web of Science, and the Cochrane Library (from January 1980 onwards). We will include randomized controlled trials, quasi-experimental studies (non-randomized, interrupted time series), and observational studies (e.g., cohort studies and case-control studies), examining the efficacy of extracranial-intracranial bypass surgery compared to other treatments for adult patients with occlusive atherosclerotic disease of anterior cerebral circulation. Two team members will independently screen all citations, full-text articles, and abstract data. Potential conflicts will be resolved through discussion. The primary outcome will include stroke or death. The secondary outcomes will include intracranial hemorrhage, transient ischemic attack, and myocardial infarction. The study methodological quality (or bias) will be appraised using appropriate tools. If feasible, we will conduct random effects meta-analysis. Additional analyses will be conducted to explore the potential sources of heterogeneity (e.g., study design, geographical location, or risk of bias). Discussion This review will evaluate the evidence on the efficacy of extracranial-intracranial bypass surgery for adult patients with occlusive atherosclerotic disease of the anterior cerebral circulation. We anticipate that our findings will be of interest to patients, their families, caregivers, healthcare professionals, and in making optimal treatment selection. Implications for future clinical and epidemiological research will be discussed. Systematic review registration PROSPERO CRD42018105513